Exploration of Mesoporous Silica-based Amorphous Solid Dispersions to Enhance Bioavailability - Mude, Gaurav Sanjayrao (Asian Journal of Pharmaceutics (AJP), 2025)
This research investigates using mesoporous silica-based amorphous solid dispersions (ASDs) to increase the bioavailability of poorly soluble drugs. Mesoporous silica is a valuable carrier for keeping active pharmaceutical ingredients (APIs) in their amorphous state, which improves solubility and dissolution rates. This is due to its vast surface area and tunable pore topologies. The development of supersaturated solutions upon interaction with aqueous media is one of the mechanisms driving this augmentation, as it considerably improves medication absorption. The study demonstrates a number of ASD preparation methods that help ensure even drug dispersion within the silica matrix, including spray drying and solvent evaporation. Scanning electron microscopy and differential scanning calorimetry are two characterization techniques used to evaluate the physicochemical characteristics of these formulations. Research both in vivo and in vitro show the research highlights various preparation techniques for ASDs, such as spray drying and solvent evaporation, which facilitate uniform drug distribution within the silica matrix. Characterization methods, including differential scanning calorimetry and scanning electron microscopy, are employed to assess the physicochemical properties of these formulations. In vitro and in vivo studies demonstrate that mesoporous silica prevents crystallization and enhances the pharmacokinetic profiles of APIs such as ritonavir and telmisartan. All things considered, the incorporation of mesoporous silica into ASD formulations offers a viable strategy for resolving the issues related to low-solubility medications, opening the door to more potent therapeutic uses. This investigation establishes the foundation for subsequent studies aimed at refining ASD formulations for an expanded array of poorly soluble chemicals.